2015
DOI: 10.1016/j.cels.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Functional Hierarchy of Redundant Actin Assembly Factors Revealed by Fine-Grained Registration of Intrinsic Image Fluctuations

Abstract: Summary Highly redundant pathways often contain components whose functions are difficult to decipher from the responses induced by genetic or molecular perturbations. Here, we present a statistical approach that samples and registers events observed in images of intrinsic fluctuations in unperturbed cells to establish the functional hierarchy of events in systems with redundant pathways. We apply this approach to study the recruitment of actin assembly factors involved in the protrusion of the cell membrane. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
139
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(149 citation statements)
references
References 36 publications
9
139
1
Order By: Relevance
“…The inhibitor SMIFH2 of formin activities prevents the formation of actin rings, and the Arp2/3 complex is associated with these rings. Formin and Arp2/3 appear to join activities in pushing the membrane of Dictyostelium cells through a hole, as they cooperate in the propagation of a leading edge in mammalian cells (Lee et al, 2015). The growth of actin filaments pointing upright from the membrane in early protrusions suggests an initial formin-driven nucleation step.…”
Section: Generation Of the Filament Arrays In Actin Ringsmentioning
confidence: 98%
See 1 more Smart Citation
“…The inhibitor SMIFH2 of formin activities prevents the formation of actin rings, and the Arp2/3 complex is associated with these rings. Formin and Arp2/3 appear to join activities in pushing the membrane of Dictyostelium cells through a hole, as they cooperate in the propagation of a leading edge in mammalian cells (Lee et al, 2015). The growth of actin filaments pointing upright from the membrane in early protrusions suggests an initial formin-driven nucleation step.…”
Section: Generation Of the Filament Arrays In Actin Ringsmentioning
confidence: 98%
“…These nucleating factors act together to coordinate leading edge protrusion. In PtK1 cells, recruitment of the formin mDia1 to the leading edge precedes actin polymerization that initiates protrusion, whereas recruitment of the Arp2/3 complex follows the protrusion onset (Lee et al, 2015).…”
Section: Generation Of the Filament Arrays In Actin Ringsmentioning
confidence: 99%
“…Although recent work has shown that the microenvironmental properties of the stroma mediate critical functions, such as drug resistance in cancer cells (Hirata et al, 2015), we have very little understanding of how a cell’s microenvironment influences the spatial and temporal organization of molecular signaling pathways. The quantitative approaches necessary to extract such spatiotemporal information have provided valuable insight into how protein spatial distribution and activity regulate cell behaviors (Lee et al, 2015; Plotnikov et al, 2012; Spiller et al, 2010; Welf and Danuser, 2014). Unfortunately, the ability to quantify cell signaling and morphological changes in 3D environments demands specific temporal and spatial resolution in imaging (Vilela et al, 2013) that is not achievable by existing microscopy approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In many cells, usually soon after they spread on a surface and before the onset of directed cell motion, the protrusion of the lamellipodium is followed by retraction (Ryan, Watanabe, & Vavylonis, ). This leads to cycles of protrusion and retraction that are periodic and in some cells organize into traveling waves of protrusion along the cell front and sides (Allard & Mogilner, ; Barnhart, Allard, Lou, Theriot, & Mogilner, ; Barnhart, Lee, Keren, Mogilner, & Theriot, ; Driscoll et al, ; Giannone et al, ; Lee et al, ; Liu, Welf, & Haugh, ; Machacek & Danuser, ; Raynaud et al ; Ryan, Watanabe, et al, ; Ryan, Petroccia, et al, ). This regular behavior involving fluctuations around a steady state can be used to study how the dynamics of actin polymerization are converted into cell motion (Ryan, Watanabe, et al, ).…”
Section: Introductionmentioning
confidence: 99%